A Legal Consequences of the Passing Off Practice of the MS GLOW Brand by the PSTORE GLOW Brand - Wibowo, Rezqiyan Bagus (Al Mashaadir : Jurnal Ilmu Syariah, 2024)
Intellectual Property Rights are essentially rights with special and special characteristics because these rights are granted by the State. A brand as an Intellectual Property Right is basically a sign to identify the origin of goods and services from a company with the goods and/or services of another company. One of the cases regarding Passing Off occurred in the Commercial Court Decision at the Medan District Court Number 2/Pdt.Sus-HKI/Merek/2022/PN Niaga Mdn. It started when Shandy Purnamasari filed a trademark cancellation lawsuit against PT PSTORE Glow Bersinar Indonesia. This lawsuit is based on the similarity of the brands "PSTORE GLOW" and "PSTORE GLOW FOR MEN" owned by Putra Siregar with the brands "MS GLOW/for pretty skincare & LOGO" and "MS GLOW FOR MEN" owned by Sandy Purnamasari. Shandy considers that PSTORE Glow Bersinar Indonesia has imitated his brand. The main problem in this research is what the legal consequences are for the practice of passing off the MS GLOW brand by the PSTORE GLOW brand. The research method used in this research is normative juridical with a case approach and a statutory approach. The research results show that as a legal consequence of the practice of passing off, the PSTORE Glow Brand and its derivatives can no longer be used, and the registration is considered invalid. Apart from the deletion of the PSTORE Glow brand, MS Glow can also file a criminal complaint in accordance with the provisions as intended in article 100 paragraph (1) and paragraph (2) of the Trademark and Geographical Indications Law and if PSTORE Glow is still selling its products after the decision to cancel the brand.